Gastric adenocarcinoma and Helicobacter pylori: Correlation with p53 mutation and p27 immunoexpression - Andre, Angela Rosa; Pitombeira Ferreira, Marcia Valeria; Salani Mota, Rosa Maria; Ferrasi, Adriana Camargo [UNESP]; Pardini, Maria Ines de Moura Campos [UNESP]; Barem Rabenhorst, Silvia Helena (Elsevier B.V., 2010)
Introduction: Helicobacter pylori infection is an established risk factor for gastric cancer development, but the exact underlying mechanism still remains obscure. The inactivation of tumor suppressor genes such as p53 and p27(KIP1) is a hypothesized mechanism, although there is no consensus regarding the influence of H. pylori cagA(+) in the development of these genetic alterations. Goals: To verify the relationship among H. pylori infection, p53 mutations and p27(Kip1) Protein (p27) expression in gastric adenocarcinomas (GA) seventy-four tissues were assayed by PCR for H. pylori and cagA presence. Mutational analysis of p53 gene was performed by single-strand conformation polymorphism (SSCP). Seventy tissues were analyzed by an immunohistochemical method for p27 expression. Results: From the samples examined, 95% (70/74) were H. pylori positive, 63% cagA(+). Altered p53 electrophoretic mobility was found in 72% of cases and significantly more frequent in the presence of cagA. Considerable reduction in p27 expression (19%) was found with a tendency for association between cagA(+) and p27(-), although the results were not statistically significant. Concomitant alterations of both suppressor genes were detected in 60% of cases. In the cases cagA(+), 66.7% of them had these concomitant alterations. Conclusions: The data suggest that H. pylori cagA(+) contributes to p53 alteration and indicate that concomitant gene inactivation, with reduced p27 expression, may be a mechanism in which H. pylori can promote the development and progression of gastric cancer. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Gastric cancer; Helicobacter pylori; Tumor suppressor genes; p53 genes; p27 Kip1 Protein